Austempering of Spheroidal Cast Iron. - Onuoha, Enyinnaya Martin (Obafemi Awolowo University, 2014)
The effect of austempering on the hardness, ultimate tensile strength and per cent elongation of twenty pre-annealed unalloyed spheriodal cast iron specimens have been investigated and evaluated. The specimens were solution treated at 800°C and 900°C, each for 10 and 90 minutes, and isothermally transformed at 300°C and 400°C for 3 hours.